Layoffs and Lemons - Gibbons, Robert; Katz, Lawrence F. (Journal of Labor Economics, 1991)
We provide theoretical and empirical analyses of an asymmetric-information model of layoffs. When firms have discretion with respect to whom to lay off, the market infers that laid-off workers are of low ability. Assuming that no such negative inference is warranted if workers are displaced in a plant closing, postdisplacement wages should be lower and postdisplacement unemployment spells should be longer for those displaced by layoffs than for those displaced by plant closings, but predisplacement wages should not differ by cause of displacement. Evidence on displaced workers from Current Population Surveys supports all three of our model's predictions.